2019
DOI: 10.1371/journal.pone.0212194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of highly active antiretroviral therapy on semen parameters of a cohort of 770 HIV-1 infected men

Abstract: Background HIV-1 infected patients show impaired semen parameters. Currently, it is not clear whether HIV-1 infection itself or antiretroviral therapy have an effect on semen parameters. We aim evaluate semen quality in a large cohort of fertile HIV-1 infected men under stable highly active antiretroviral therapy (HAART) and to assess the effect of HAART type and duration on semen parameters. Materials and methods Between January 2010 and June 2014, we enrolled in a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 28 publications
4
24
0
Order By: Relevance
“…The present manuscript represents an introductory report on the development and methodology of the "EAA ultrasound study" (http:// www.andro logya cademy.net/studi es) 23 The main characteristics of the semen parameters found in the cohort were consistent with those reported by the WHO 7 for both the 50th and the 5th centiles for fertile men. This is relevant, because in other studies [50][51][52] comparing their data with those of the WHO 7 the mean or median values of the semen parameters of the investigated cohort were consistent with those of the WHO, 7 but there was a higher prevalence of subjects with seminal values below the 5th centile than in the present study.…”
Section: Discussionsupporting
confidence: 72%
“…The present manuscript represents an introductory report on the development and methodology of the "EAA ultrasound study" (http:// www.andro logya cademy.net/studi es) 23 The main characteristics of the semen parameters found in the cohort were consistent with those reported by the WHO 7 for both the 50th and the 5th centiles for fertile men. This is relevant, because in other studies [50][51][52] comparing their data with those of the WHO 7 the mean or median values of the semen parameters of the investigated cohort were consistent with those of the WHO, 7 but there was a higher prevalence of subjects with seminal values below the 5th centile than in the present study.…”
Section: Discussionsupporting
confidence: 72%
“…In fact, spermatozoa lack an HIV receptor and therefore the male gametes themselves are not infected as the virus is only present in seminal plasma [ 101 ]. Even though sperm processing by density gradient can yield viral-free samples safe for insemination and a seronegative offspring has been born from IUI using decontaminated spermatozoa from seropositive male [ 102 ], patients treated with HAART may present with impaired semen parameters including volume, concentration, progressive motility and compromised morphology [ 103 ]. In addition to an already impaired semen sample, proper sperm processing is required to remove excess viral particles, resulting in loss of additional sperm cells, leaving ICSI as the preferable insemination option to ensure successful treatment outcome [ 99 , 104 , 105 ].…”
Section: Male Factors Indications Of Icsimentioning
confidence: 99%
“…Still, information is lacking on the long-term effects of ARVs alone or in mixture with other pharmaceuticals in surface water on fish reproduction. Different studies on human HIV patients have argued that the ARVs treatment may have effects on the reproductive system which may be the cause of infertility cases observed in many HIV/AIDS patients ( Pavili et al., 2010 ; Kushnir and Lewis 2011 ; Savasi et al., 2019 ). Studies on the reproductive system of HIV/AIDS patients have shown abnormalities in male semen and female oocyte mitochondrial DNA as well as histopathological changes in the seminiferous tubules ( Da Silva et al., 1990 ; Azu 2012 ; Savasi et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies on human HIV patients have argued that the ARVs treatment may have effects on the reproductive system which may be the cause of infertility cases observed in many HIV/AIDS patients ( Pavili et al., 2010 ; Kushnir and Lewis 2011 ; Savasi et al., 2019 ). Studies on the reproductive system of HIV/AIDS patients have shown abnormalities in male semen and female oocyte mitochondrial DNA as well as histopathological changes in the seminiferous tubules ( Da Silva et al., 1990 ; Azu 2012 ; Savasi et al., 2019 ). Studies with laboratory rats treated with ARVs have also reported histological alterations of seminiferous tubules and a decrease in sperm motility ( Adaramoye et al., 2012 ; Azu et al., 2014 ; Oyeyipo et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%